L' évolution religieuse en milieu rural - Laloux, Joseph (Social compass, 1961)
The analysis of external and internal patterns of con duct in the observation of religious duties (especially mass attendance on Sunday) shows typical differencies in time, space, and from one social category to another. There exists also a difference of rhythm in their evolution, between external and internal pat terns. From these considerations, both theoretical and pratical, the A. makes some pertinent conclusions on the adaptation of pastoral work in rural countries.